Buildings Sustainability — The Non-Intrusive Load-Identification System Contribution - Felgueiras, Manuel Carlos (2017)
Buildings are responsible for an important share of the global energy consumed with the associated consequences at economic and environmental level. To overcome this actual concern several objectives were put in perspective, being one of them the energetic performance of systems and appliances. Efficiency depends on working on optimal conditions and user behavior. Monitoring of the energy consumption of each electric load is important but the use of decentralized energy is not feasible at present due to the huge number of loads connected to the electric grid. An alternative consists on the use of a centralized measurement device able to identify loads. This work presents a measurement infrastructure that have, among others, the possibility to make the identification of electrical loads data will be used to improve the energetic performance of households and buildings and increase the sustainability of the energy system.